A conceptual analysis of public opinion regarding genome research in Japan - Shahrier, Shibly; Gaydarska, Hristina; Takashima, Kayo; Yoshizawa, Go; Minari, Jusaku (Frontiers in Genetics, 2023)
In the twenty years since the completion of the Human Genome Project, the gap between scientific development and public understanding of genome research has been widening. While genome research has been increasingly utilized for social and clinical purposes in a multifaceted manner, these attempts have also resulted in an increase in the potential risks associated with genomic data. In this context, our study aims to consider the nature of public perceptions of genome research, primarily by using the results of previous public surveys, which are relevant to donations for social benefits in Japan, as a case study. In this study, we explored certain types of awareness, attitude, and intention (A-A-I) on such surveys and discussed the resultant key findings through the cultural transmission framework. Reframing the public’s response toward genome research based on A-A-I analysis and behavioral science may contribute to developing more systematic communication approaches with the public. With a view to establishing such approaches, our perspective suggests some new insights to discuss the science-society gap in genome research internationally.